Challenges and the Urgency of Regulatory Reform for Ad Hoc Election Bodies: A Case Study of Luwu Regency - Djidar, Haedar; Rahman Nur, Abdul; Kamal, Kasmad; Suhaeb (Journal of Social and Policy Issues, 2025)
This study aims to analyze the strategic role of Ad Hoc election bodies in the implementation of General Elections in Luwu Regency, as well as to identify the challenges encountered throughout the election process. The research adopts a normative-empirical legal method, employing statutory, historical, comparative, and conceptual approaches. Data were collected through the examination of primary and secondary legal materials, which were systematically analyzed to address legal issues and practical conditions in the field. The findings reveal that Ad Hoc election bodies play a crucial and decisive role in ensuring the success and credibility of electoral processes. However, their legal status and authority are not yet explicitly and comprehensively regulated under Law Number 7 of 2017 on General Elections. Furthermore, budget limitations significantly affect various aspects of election administration, including the training of election officers, the quality of logistical arrangements, and the integrity of vote casting and counting processes. Therefore, it is necessary to revise the existing law to reinforce the legal framework governing Ad Hoc election bodies and ensure adequate budget allocation to support an efficient, transparent, and accountable election process. Legal protections must also be strengthened to prevent any form of intervention or intimidation against Ad Hoc election bodies during all election stages.